Evaluation of the warranty cost of a product with type III stochastic dependence between components - Zhang, Nan; Fouladirad, Mitra; Barros, Anne (Applied Mathematical Modelling, 2018)
•Warranty policy analysis.•Two component system with stochastic dependency.•Renewal theory and Manufacturer and User cost calculation.•Non constant Failure rate and Accumulative damage. This paper analyses respectively the expected warranty costs from the perspectives of the manufacturer and the consumer. For a two-component series system with stochastic dependence between components, both the non-renewing free replacement policy and the renewing replacement policy are examined. It is assumed that whenever component 1 fails, a random damage to component 2 is occurred while a component 2 failure causes the system failure. Component 2 fails when its total accumulative damage exceeds a pre-determined level L. By considering the consumer’s behavior and the product service time, the warranty costs allocations between the manufacturer and the consumer are presented. Numerical examples are given to demonstrate the applicability of the methodology. It is proved that, independent of the type of the warranty policy, the failure interaction between components impacts the manufacturer profits and the consumer costs. The initial warranty length has also an impact on the product quality preferences to both the consumer and the manufacturer.